Transactional Sex, Digitalization and Administration in Selected Tertiary Institutions, Southwest Nigeria - Augusta Odiche Diala (Universitas Medan Area, 2025)
This study examines the complex intersection between transactional sex, digitalization, and institutional administration in selected tertiary institutions in Southwest Nigeria. While e-administration initiatives are increasingly adopted to enhance service delivery and academic transparency, unintended consequences have surfaced, notably the rise in transactional sexual relationships. These relationships, often involving the exchange of sex for material benefits or academic favors, are now frequently facilitated by digital platforms such as social media and mobile banking, complicating oversight and ethical governance in higher education. Grounded in Bronfenbrenner’s Bio-ecological Systems Theory and Technological Determinism Theory, the study provides a theoretical lens for understanding how multi-layered social environments and advancing digital technologies interact to shape student behaviors, power dynamics, and exploitative practices within educational settings. Using a qualitative research design, in-depth interviews were conducted with 30 students (25 female, 5 male) across five universities. Findings revealed six major themes: students’ perceptions of transactional sex, its root causes, associated health risks, proposed remedies, perceptions of digitalization, and its challenges. Transactional sex emerged as a survival strategy driven by poverty, peer influence, social norms, and digital anonymity. Reported implications included gender-based violence, unwanted pregnancies, sexually transmitted diseases (such as HIV/AIDS), and academic decline. At the same time, participants acknowledged digital learning’s flexibility and administrative efficiency but noted concerns regarding digital distractions, infrastructure deficits, and weakened interpersonal relationships. The study concludes that while digitalization promotes institutional efficiency, it also inadvertently fosters exploitative behaviors that threaten student welfare and institutional integrity. It recommends behavior change campaigns targeting students and parents, university-based health education programs, and poverty alleviation initiatives, such as scholarships, vocational training, and regulatory safeguards, to promote ethical conduct, protect vulnerable groups, and strengthen academic integrity.